An analysis of adult ESL short-course students' identities as writers - Slater, Sanchia (My University, 2014)
The present study investigated how adult speakers of English as a second language in South Africa perceive and construct themselves as writers in English. Two ‘writing autobiographies’ provided insight into participants’ perceptions of themselves as writers in English as well as the writing experiences that contributed to these beliefs. A thematic content analysis of the data revealed four thematic networks, each clustering around a global motif. Writing was seen to be a public presentation and representation of individual meaning and ability and although participants appeared to view themselves as not yet proficient in the skills necessary for effective writing, this was mitigated by a sense of resilience in the face of negative educational and feedback experiences together with the belief that personal effort was instrumental in strengthening writing skills and abilities. The theory of self-efficacy was found to be a powerful concept that accounted for many of the themes that emerged from the data. Further research into the self-efficacy beliefs of adult ESL writers is recommended.